2010
DOI: 10.1016/j.ijrobp.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Local Failure With Measures of Dose Insufficiency in the High-Dose Single-Fraction Treatment of Bony Metastases

Abstract: Purpose In the setting of high-dose single-fraction image-guided radiotherapy of spine metastases, the delivered dose is hypothesized to be a significant factor in local control. We investigated the dependence of local control on measures of dose insufficiency. Methods and Materials The minimum doses received by the hottest 100%, 98%, and 95% (Dmin, D98, and D95) of the gross target volume (GTV) were computed for 91 consecutively treated lesions observed in 79 patients. Prescribed doses of 18–24 Gy were deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…7 The difference in tumor arrest mechanisms may account for the finding that SRS provides improved local tumor control irrespective of histology and size, which differs from the results observed with conventional fractionation. 4,19,28,30 Because SRS provides local tumor control irrespective of the tumor volume, the extent of tumor resection loses importance as long as there is adequate separation of the tumor from vital structures to allow for optimal radiation dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…7 The difference in tumor arrest mechanisms may account for the finding that SRS provides improved local tumor control irrespective of histology and size, which differs from the results observed with conventional fractionation. 4,19,28,30 Because SRS provides local tumor control irrespective of the tumor volume, the extent of tumor resection loses importance as long as there is adequate separation of the tumor from vital structures to allow for optimal radiation dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…Initial clinical results from prospective single institution, and more recently, multi‐institutional clinical trials of SABR have documented high rates of tumor control coupled with a low incidence of serious toxicity despite the high‐dose fractions of radiation being delivered. In the setting of early stage lung cancer, three‐year local control rates of 88% to 97% have been reported 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…even the "high dose" approach of 40 Gy in 20 fractions would result in tumor control of less than 5% for NSCLC [33]. This hypothesis is supported by three studies, which reported a significant dose response relationship for primary [17,31] and re-irradiation [34] spine radiosurgery. The Memorial Sloan-Kettering Cancer Center (MSMCC) group reported excellent local control of > 95% for a prescription dose of 24 Gy and a minimum dose of > 15.1 Gy; however, the results are based on a retrospective review of serially dose-escalated patients and require validation before conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 93%